Early health issues in late pre-terms - Choudhary, Monica; Jain, Kamna (International Journal of Contemporary Pediatrics, 2019)
Background: Rates of preterm birth are increasing worldwide, mostly due to late preterm births (i.e. 34-36 6/7 weeks). The objective of the study is to calculate incidence of early morbidity and mortality in late preterm neonates (within first 7 days of life) compared with term neonates. Methods: It was a prospective cohort study. All live inborn late preterm infants (34 0/7 to 36 6/7 weeks) and term infants (37 0/7 to 41 6/7 weeks) who were born between November 2010 to October 2011. Study was done to find out early morbidity and mortality in late preterm births. Results: Present study included 256 late preterm infants and 498 term infants, amongst whom 95 (37.10%) late preterm and 98 (19.67%) term infants required NICU care (p<0.001). Late preterm infants were at significantly higher risk for overall morbidity due to any cause (P<0.001; Odds Ratio (OR):2.4; 95% CI: 1.7-3.3), respiratory morbidity (P<0.001; OR:3.64; 95% CI:1.7-7.4), neonatal depression (p<0.001; OR:2.94; 95% CI:1.00-8.62), any resuscitation/ventilation (P<0.05; OR: 3.1; 95% CI:1.15-8.31), probable sepsis (P<0.001; OR:11.2; 95% CI:2.5-49.8), confirmed sepsis (p=0.05; OR:7.7; 95% CI:0.9-63.9), or other problems like jaundice, hypoglycemia, hypothermia and feeding difficulty. The incidence of morbidity increased as gestational age decreases from 19.67% in term infants (>37 weeks) to 27.8%, 43%, 54.5% at 36, 35 and 34 weeks, respectively (P<0.001). Conclusions: The morbidity risk in late preterm births is 1.3 times more at 36 weeks, 2 times more at 35 weeks and 2.7 times more at 34 weeks as compared with term neonates. The mean cost of stay increased 1.8 times in the late preterm neonates as compared to the term neonates.